2009
DOI: 10.1007/s00128-009-9691-y
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Polychlorinated Biphenyls in the Rhizosphere of Rape, Brassica napus L.

Abstract: The objective of this study was to investigate the rhizosphere effect of rape plants on polychlorinated biphenyls (PCB) dissipation in soils spiked with seven indicator congeners. Depletion of PCB in the rhizosphere was significantly higher in the soil with lower organic matter content. While in the Chernozem soil, 87% of PCB related to bulk soil were found in the 1st mm from roots, only 62%-69% were found in the Fluvisol soil with no significant influence of increased initial PCB concentration. Further from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…For example, the concentration of PAHs has been shown to decrease logarithmically when moving toward the surface of a ryegrass root (Joner and Leyval, 2003) It also demonstrated that effects of degradation and dissipation leads to the concentration of PCBs in RS being lower than in bulk soils (Javorska et al, 2009). However, evidence of the rhizosphere effect on the release of adhered PBDEs in historically contaminated soil has also been reported previously .…”
Section: Rhizosphere Effectmentioning
confidence: 99%
“…For example, the concentration of PAHs has been shown to decrease logarithmically when moving toward the surface of a ryegrass root (Joner and Leyval, 2003) It also demonstrated that effects of degradation and dissipation leads to the concentration of PCBs in RS being lower than in bulk soils (Javorska et al, 2009). However, evidence of the rhizosphere effect on the release of adhered PBDEs in historically contaminated soil has also been reported previously .…”
Section: Rhizosphere Effectmentioning
confidence: 99%
“…Degradation or adsorption may vary among plant species and varieties (Wiltse et al, 1998;Liste and Alexander, 2000); the different sampling procedures of the rhizosphere soil may also lead to results that cannot be directly compared. Javorska et al (2009) and Ma et al (2010) demonstrated that the effects of degradation and dissipation led to PCB and PAH concentrations in the rhizosphere soils that were lower than in the bulk soils. Joner and Leyval (2003) also assumed that the PAH concentrations decreased logarithmically while moving towards the root surface.…”
Section: Levels Of Pbdes In the Rhizosphere And Non-rhizosphere Soilsmentioning
confidence: 99%
“…and PCB 138 represent plants PCBs profile. The mobility of PCB 153 could be favored due to its symmetrical structure [19].…”
Section: Assessment Of Pcbs Distribution In Plantmentioning
confidence: 99%